Phase 1 study of cetuximab in combination with 5‐fluorouracil, cisplatin, and radiotherapy in patients with locally advanced anal canal carcinoma. Issue 16 (14th May 2013) - Olivatto, Luis O.; Vieira, Fernando M.; Pereira, Bruno V.; Victorino, Ana P.; Bezerra, Marcos; Araujo, Carlos M.; Erlich, Felipe; Faroni, Lilian; Castro, Leonaldson; Lusis, Edward C.; Marins, Alessandra; Ferreira, Carlos Gil
<x xml:space="preserve">Abstract</x> BACKGROUND This study sought to determine the feasibility and recommended phase 2 dose (RP2D) of the combination of cetuximab with chemoradiotherapy based on 5‐fluorouracil (5‐FU) and cisplatin (CP) in locally advanced anal canal carcinoma. METHODS Cetuximab was administered on days 1, 8, 15, 29, 36, 43, and 50 (400 mg/m2 initial dose, then 250 mg/m2/week) concurrent with total dose radiation of 55 to 59 Gy, both starting on day 1. Escalating doses of 5‐FU (96‐hour infusion) and CP (2‐hour infusion), both on days 1 and 29, were administered according to the following design: starting dose level (0) 5‐FU/CP = 800/60 mg/m2/day and up to dose level (+2) 5‐FU/CP = 1000/80 mg/m2/day. RESULTS Dose‐limiting toxicity (DLT) events (uncontrolled diarrhea or febrile neutropenia) occurred in 3 of 14 assessable patients receiving escalated dose of 5‐FU/CP, with 1 in dose level (0) and 2 in dose level (+2). The RP2D was 5‐FU/CP = 800/80 mg/m2/day. Because of unexpected non‐DLT treatment‐related grade 3 (G3) adverse events (AEs) such as thrombosis/embolism, syncope, and infection occurring in ≥ 20% of patients, a safety expansion cohort with an additional 9 patients was investigated with the RP2D. The most frequent G3/G4 AEs evaluated in 23 patients were radiation dermatitis (12 patients), diarrhea (10 patients), thrombosis/embolism (6 patients), and infection (5 patients). The study was closed due to these severe AEs, although no G5 AEs occurred. Twenty of 21 patients (95%) achieved pathological complete response at primary tumor. With a median follow‐up of 43.4 months, the 3‐year locoregional control rate was 64.2%. CONCLUSIONS Cetuximab could not be integrated with chemoradiotherapy‐cisplatin–based therapy due to the high toxicity rate. However, efficacy is encouraging and further investigation of an epidermal growth factor receptor–targeted agent (other than cetuximab) concurrent with chemoradiation should be pursued. Cancer 2013;119:2973—2980. © 2013 American Cancer Society.